Web-based reading and writing activities: supporting the learning of english as a foreign language (EFL) for students of 10th year of basic education at Unidad Educativa Salesiana María Auxiliadoa (UESMA) - Álvarez Toromoreno, Karina Elizabeth
This thesis investigates the effective development of EFL reading and writing skills designed for students from 10th class at Unidad Educativa Salesiana María Auxiliadora (UESMA) in Cuenca, Ecuador, through the implementation of web-based activities as a tool to support the process. The application of surveys and questionnaires, as well as the analysis of students? written work provide data to recognize the problem and its implications in the development of the above mentioned skills. The present research work is developed as follows: Chapter 1 deals with the definition of the problem, the justification and the objectives. Chapter 2 is concerned with the study and review of scientific theories of relevance to the research. In Chapter 3 the data collection of students? EFL learning difficulties and the analysis of students? learning styles serve as a base for the design of the web-based activities. Chapter 4 shows the benefits obtained through their application and use with students from 10th grade in order to support the hypothesis that argues for having a virtual learning environment (VLE) as a resource of teaching material. Finally, Chapter 5 communicates the conclusions drawn from the essential points developed throughout the research process. Additionally, some recommendations for future use in other institutions are given.